Pengaruh Pertumbuhan Ekonomi dan Jumlah Wajib Pajak terhadap Kinerja Keuangan Pemerintah Kabupaten Banjar Tahun 2015-2020 - Miftahuddin*,; Ahmad Yunani (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to determine the classification of government financial performance and the effect of economic growth and the number of taxpayers on the government's financial performance of the Banjar Regency Government in 2015-2020. The analytical method analyzes local government financial performance and multiple linear regression. The results showed that the classification of the financial performance of the Banjar Regency government in 2015- 2020, on average, was in the medium category. In multiple linear regression analysis, it is known that economic growth and the number of taxpayers affect the financial performance of the Banjar Regency government. This shows that there needs to be an effort by the government to improve financial performance by taking policies that can improve the financial performance of local governmentslocally.